2013
DOI: 10.1152/ajpheart.00987.2012
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates vascular adaptive mitochondrial dynamics

Abstract: Miller MW, Knaub LA, Olivera-Fragoso LF, Keller AC, Balasubramaniam V, Watson PA, Reusch JE. Nitric oxide regulates vascular adaptive mitochondrial dynamics. Am J Physiol Heart Circ Physiol 304: H1624 -H1633, 2013. First published April 12, 2013 doi:10.1152/ajpheart.00987.2012.-Cardiovascular disease risk factors, such as diabetes, hypertension, dyslipidemia, obesity, and physical inactivity, are all correlated with impaired endothelial nitric oxide synthase (eNOS) function and decreased nitric oxide (NO) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 67 publications
5
57
0
1
Order By: Relevance
“…On the contrary, the known vasorelaxants nitroglycerin and ROCK inhibitor Y27632 not only relaxed KPSS-induced aorta constriction but also inhibited KPSS-induced increase of mitochondrial fission in smooth muscle cells of rat aorta and cultured arterial smooth muscle cells. It was reported that NO inhibited mitochondrial fission 17,18 and ROCK activation induced mitochondrial fission. 19,20 Although nitroglycerin and Y27632 have different mechanisms of vasorelaxant effects, both of them inhibited mitochondrial fission.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, the known vasorelaxants nitroglycerin and ROCK inhibitor Y27632 not only relaxed KPSS-induced aorta constriction but also inhibited KPSS-induced increase of mitochondrial fission in smooth muscle cells of rat aorta and cultured arterial smooth muscle cells. It was reported that NO inhibited mitochondrial fission 17,18 and ROCK activation induced mitochondrial fission. 19,20 Although nitroglycerin and Y27632 have different mechanisms of vasorelaxant effects, both of them inhibited mitochondrial fission.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it is important to note that NO is an important inducer of mitochondrial biogenesis in vascular tissues through direct activation of PGC-1␣ (30). A recent study showed that eNOS inhibition attenuated mitochondrial adaptation to an exercise intervention in the aorta (26). Therefore, it is possible that LSS-induced SIRT1 activation contributes to the preservation of EC function via activation of a SIRT1/eNOS/PGC-1␣ signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…By initiating downstream cGMP/PKG signaling, NO stimulates peroxisome proliferator-activated receptor γ coactivator 1α, which in turn activates nuclear peroxisome proliferator-activated receptor-γ receptors enhancing the synthesis of mitochondrial DNA and proteins (eg, complexes I-IV of the electron transport chain), thereby contributing to the maintenance of the mitochondrial mass and its function (including regulation of the cellular production of reactive oxygen species [ROS] and energy metabolism). [62][63][64] Overall, in terms of local vasomotor control, with few exceptions (see Vasoconstrictor Effect section of this article), NO is a powerful vasodilator that prevents or reduces vasoconstrictions.…”
Section: Normal Responses To Endothelium-derived Nomentioning
confidence: 99%